Development of Pop-up Book Media for Islamic Religious Education Learning in Junior High Schools - Muliani, Muliani; Sabani, Fatmarida (Educational Journal of Learning Technology, 2025)
This study aims to develop pop-up book media on Prayer and Zikir material in Islamic Religious Education in grade VII of SMP Negeri 4 Angkona and evaluate its validity and practicality. This study uses a quantitative Research and Development (R&D) method based on the 4D model (Define, Design, Develop, Disseminate). Data was collected through observation, documentation, and questionnaires and then analyzed in a quantitative descriptive manner. The study results show that the steps to develop Pop Up Book media follow the stages of a 4D model. This media has an excellent level of validity, with a rating of 75% from media experts and 100% from material experts. This pop-up book media has proven to be effective and practical in supporting Islamic Religious Education learning, so it can be an innovative solution to increase students' interest in and understanding of the material.